Exercise, nutrition and enzyme replacement therapy are efficacious in adult Pompe patients: report from EPOC Consortium - Corrado Angelini (PAGEPress Publications, 2021)
Pompe Disease, also known as glycogenosis type 2, is due to deficiency in lysosomal alpha- glucosidase, a lysosomal hydrolase, which presents infantile and late onset subtypes (LOPD). The myopathy in LOPD can be reversed by Enzyme Replacement Therapy (ERT), but might benefit from a concomitant low carbohydrate - high protein diet and aerobic exercise treatment. From 65 Late onset Pompe cases, we were able to obtain in 58 a self-reported evaluation, most of them gave a positive efficacy evaluation of Enzyme Replacement Therapy and they were classified by a self-administered scale as Responders or non-Responders. A cooperative study of a clinical group on LOPD monitored age, sex, BMI, Gardner-Medwin-Walton scale and six minute walking test (6MWT). The only clinical parameters that were significantly associated with a Responder category were the pre-ERT walking distance (p<0.035) and the use of regular diet, exercise or both (p<0.029). The present study shows that in LOPD this condition can be treated by ERT, but also benefits from concomitant diet and aerobic exercise therapy.